Ethical reflections on Covid-19 vaccines. Issue 3 (4th May 2022) - Raus, Kasper; Mortier, Eric; Eeckloo, Kristof
ABSTRACT: Objectives: More than 1 year after the start of the Covid-19 pandemic it is becoming increasingly clear that vaccines will prove to be essential in combating this global pandemic. The demand for such vaccines is great (since nearly everyone is a candidate for vaccination) yet supplies are currently limited. This raises clear ethical questions regarding the current and future Covid-19 vaccines. Methods: In this paper we highlight the several ethical questions that are raised using a three-fold categorization. We will discuss questions concerning: (1) the design and testing of vaccines; (2) who gets the vaccines; and (3) the tensions between public health and individual interest/autonomy. Each of these three more broad categories encompasses many different and concrete ethical questions. Results: We argue that different ethical frameworks apply both across these three categories, but also within these categories. Conclusion: Despite the fact that ethical conflict might not completely disappear, we argue that distinguishing and discussing separate questions from an ethical perspective can help create the necessary clarity and provide an ethical justification in favour of particular vaccination issues.